Multiple timescales of stochastically forced North Atlantic Ocean variability: A model study - Mecking, Jennifer; Keenlyside, Noel S.; Greatbatch, Richard John (Ocean Dynamics, 2015)
The Atlantic meridional overturning circulation (AMOC) and the subpolar gyre (SPG) are important elements in mechanisms for multidecadal variability in models in the North Atlantic Ocean. In this study, a 2000-year long global ocean model integration forced with the atmospheric patterns associated with a white noise North Atlantic Oscillation (NAO) index is shown to have three distinct timescales of North Atlantic Ocean variability. First, an interannual timescale with variability shorter than 15 years, that can be related to Ekman dynamics. Second, a multidecadal timescale, on the 15- to 65-year range, that is mainly concentrated in the SPG region and is controlled by constructive interference between density anomalies around the gyre and the changing NAO forcing. Finally, the centennial timescales, with variability longer than 65 years, that can be attributed to the ocean being in a series of quasi-equilibrium states. The relationship between the ocean’s response and the NAO index differs for each timescale; the 15-year and shorter timescales are directly related to the NAO of the same year, 15- to 65-year timescales are dependent on the NAO index in the last 25–30 years in a sinusoidal sense while the 65-year and longer timescales relate to a sum of the last 50–80 years of the NAO index.